The mitochondrial pentatricopeptide repeat protein PPR19 is involved in the stabilization of NADH dehydrogenase 1 transcripts and is crucial for mitochondrial function and Arabidopsis thaliana development. Issue 1 (23rd March 2017) - Lee, Kwanuk; Han, Ji Hoon; Park, Youn‐Il; Colas des Francs‐Small, Catherine; Small, Ian; Kang, Hunseung
Summary: Despite the importance of pentatricopeptide repeat (PPR) proteins in organellar RNA metabolism and plant development, the functions of many PPR proteins remain unknown. Here, we determined the role of a mitochondrial PPR protein (At1g52620) comprising 19 PPR motifs, thus named PPR19, in Arabidopsis thaliana . The ppr19 mutant displayed abnormal seed development, reduced seed yield, delayed seed germination, and retarded growth, indicating that PPR19 is indispensable for normal growth and development of Arabidopsis thaliana . Splicing pattern analysis of mitochondrial genes revealed that PPR19 specifically binds to the specific sequence in the 3′‐terminus of the NADH dehydrogenase 1 ( nad1 ) transcript and stabilizes transcripts containing the second and third exons of nad1 . Loss of these transcripts in ppr19 leads to multiple secondary effects on accumulation and splicing of other nad1 transcripts, from which we can infer the order in which cis ‐ and trans ‐spliced nad1 transcripts are normally processed. Improper splicing of nad1 transcripts leads to the absence of mitochondrial complex I and alteration of the nuclear transcriptome, notably influencing the alternative splicing of a variety of nuclear genes. Our results indicate that the mitochondrial PPR19 is an essential component in the splicing of nad1 transcripts, which is crucial for mitochondrial function and plant development.